A survey of dental public health specialists on current dental public health competencies. (September 2016) - Mascarenhas, Ana Karina; Altman, Donald
Abstract: In preparation to update the Dental Public Health specialty competencies, the Expert Panel determined that a needs assessment be conducted. A nine item open and close ended survey developed by the Expert Panel was used to collect data on the Diplomates current work environment, the utility of the current set of Dental Public Health competencies, and to identify any gaps in the current competencies. In 2015, the survey was administered to all active Diplomates of the American Board of Dental Public Health. One hundred and nine Diplomates responded. Diplomates overwhelmingly reported that each of the ten current competencies were still relevant for Dental Public Health specialists in the 21 st Century, but needed to be updated to be more contemporary. Domains suggested to achieve this were interprofessional care, cultural competency, health literacy, and evidence‐based dentistry.